EFFECT OF STOCK MARKET VOLATILITY ON PROFITABILITY OF LISTED COMMERCIAL BANKS IN KENYA - RIMU, TIMOTHY MAINA (KABARAK UNIVERSITY, 2016)
The banking system plays a crucial role for any economy and any form of disruption in its functioning would have negative effects on the whole economy. It is therefore important to know the factors that influence the performance of the banking sector since identifying these determinants of bank performance is an important predictor of unstable economic conditions that would have negative effects on the banking sector. The objectives of this study were to examine the effects of stock market volatility on bank profitability of NSE-listed commercial banks in Kenya. More specifically, the study sought to establish the extent to which stock market return volatility, stock market capitalization; stock market turnover and stock market trading volume affect the profitability of commercial banks. Quantitative research design was adopted for this study where all the ten commercial banks listed in the Nairobi Securities Exchange for the period 2004 to 2014 were targeted for study. Secondary Data was collected from the NSE and published financial statements from the companies’ websites. Data collected was analyzed by use of descriptive and inferential statistics. The study applied generalized methods of moments (GMM) system estimator regression models to investigate the relationship between the independent variables and the dependent or variable. The research findings indicate that there is significant relationship between stock market volatility and stock market turnover, and bank profitability measured by ROAA. Stock market capitalization and stock market trading volume were found to insignificant in explaining the dependent variable ROAA. The implication of these findings is that variation in the stock market distorts the profitability of commercial banks significantly. However, a fundamental understanding of stock market volatility and its effect on bank performance is crucial for decision makers to undertake rational thinking before undertaking any financial decision. Appreciation of the economic conditions is paramount since it that can either initiate or truncate a company’s growth. This study therefore recommends for similar studies to be carried out in Kenya so as to analyze the impact of the other specific factors that can influence profitability of commercial banks such the recent capping of interest rates by the government.
FULL TEXT
Keywords: Stock Market volatility, Commercial Banks, Nairobi Securities Exchange, Profitability.